Indisciplina e violência na escola : concepções e discursos de educadores - Vergna, Ariel Cristina Gatti (2016)
This research aimed at analyzing the teachers‟ discourses from a state school at the interior of São Paulo State as their understandings about conflict, indiscipline and / or violence inside the school and investigate if these conceptions are reflected in their practices, when dealing with the occurrences of these events in their space. It is characterized for being a qualitative study, using two methodological instruments: a documental analysis, a survey of cases of indiscipline and violence through occurrences‟ folder; and two focus groups: one with the management staff of the school (the School‟s Mediator, the Coordinators of Elementary School I, II and High School, and the Coordinator of Support to the Management staff); and the other, with their teachers.The results were analyzed from the perspective of French Analysis of the Discourse, which allowed us to understand the speech of those educators as follows: their understandings were not the same, there were several contradictions with strong prospects for relations of power. The cases of violence officially registered in the researched school were or sporadic, or were being veiled by educators. Mainly for the management team indiscipline is related to the students‟ learning, and for teachers, by the other hand, the disrespect that occurs between students ends up generating violence in school spaces; There was no standardization for actions taken as indiscipline and / or violent at school, the individual perception of who registered determined the situation and decision-making of theses educators. It was possible to check that students were hardly heard, or had few real opportunities for participation and dialogue. It was only up to managers the deciding of what would be done ahead in the instances of conflict or violence, in order that the matter be solved within by the direction and school coordination. We conclude that, at the school studied, there was a speech of appreciation of the dialogue as a solution tool for cases of conflict, indiscipline and violence, but behind this design, the various power relations that develop within the school environment are still implicit and rooted both with respect to students and teachers, and between these teachers and management.